Exploring anesthesiology nurse' presenteeism in China: cross-sectional study - Ren Jianlan; Yuan Mei; Yang Chunyan; Xie Rendie; Bai Yiping; Liu Li (BMC, 2024)
Abstract Background The department of anesthesiology is the main battlefield for the treatment of acute and critical patients, with high work risk and high work pressure. Due to the particularity of the working environment and nature of work, medical staff have become a group with a high incidence of occupational exhaustion and presenteeism. Objective To investigate the current status of presenteeism among anesthesiology nurses in China and to analyze the related influencing factors. Methods Three hundred twelve anesthesiology nurses in Sichuan Province were surveyed by means of general data questionnaire, presenteeism scale, work-family conflict scale, perceived social support scale, occupational commitment scale and stress resistance scale from September to November 2023 by convenience sampling method. Results The total score of presenteeism was (14.67 ± 3.92), the score of work-family conflict was (45.44 ± 15.90), the score of professional commitment was (87.28 ± 14.30), and the score of perceived social support was (66.04 ± 12.78). The evaluation score of stress resistance was (73.35 ± 11.54). The results of multivariate analysis showed that age, education, mode of employment, position, overtime hours per week, work-family conflict, perceived social support and stress resistance were the factors that affected the presenteeism of anesthesiology nurses, which could explain 44.1% of the total variation. The position ( β = 0.296, P < 0.001), overtime hours per week (h) ( β = 0.271, P < 0.001), perceived social support ( β = -0.279, P < 0.001) turned out as the stronger predictors of presenteeism. Conclusion The presenteeism of anesthesiology nurses is at a high level and needs to be further improved. Clinical nursing managers should pay attention to the physical and mental health and special needs of anesthesiology nurses. Interventions are made according to the main influencing factors, so as to reduce the incidence of presenteeism and improve the quality and safety of surgery.